Modelling Monospony on the Labor Market with Separable Matching Models - Pauline Corblet; Arnaud Dupuy (Institute of Labor Economics (IZA), 2024)
We model monopsony on the labor market using a separable matching model a la Choo and Siow (2006). We propose a simple method that estimates 1) the multidimensional determinants of productivity and non-wage preferences separately and 2) the variance of unobserved heterogeneity on both sides of the market. Simulations show the effectiveness of the method. An application to Portuguese data reveals that the variance of unobserved heterogeneity is one order of magnitude larger for workers than for firms and represents about 29% of the variance in nonwage preferences of workers, while observed characteristics of workers and firms explain 71%.
Keywords: C25; C78; J28; J31; J32; 330; monopsony; amenities; matching models; unobserved heterogeneity; Pseudo-Poisson Maximum Likelihood